Steel plate and its manufacturing method
A steel plate with a polyolefin wax and organic resin film improves lubricity and formability, addressing mold galling and breakage issues, and ensuring stable adhesion and removability for complex molding.
Patent Information
- Application Number
- JP2023539323
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2023-03-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-03-15
AI Technical Summary
Existing steel plates face challenges in press formability during complex molding, leading to issues like mold galling and breakage, and require improved lubricity without surface treatment, which current technologies do not adequately address.
A steel plate with a surface film containing polyolefin wax with a specific melting point and particle size, combined with an organic resin, is applied to enhance lubricity and formability, ensuring stable adhesion and removability.
The solution significantly reduces friction, enhances press formability, and ensures good film removability, making it suitable for complex forming and automotive applications.
Smart Images

Figure 0007616392000006 
Figure 0007616392000007 
Figure 0007616392000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel sheet having excellent sliding properties in press forming, and a manufacturing method thereof, and in particular to a steel sheet having a lubricating film that exhibits excellent formability even during severe drawing, and a manufacturing method thereof. [Background technology]
[0002] Cold-rolled steel sheets and hot-rolled steel sheets are widely used in a wide range of fields, mainly for automobile body applications, and in such applications, they are subjected to press forming before use. In recent years, there has been a demand for the integration of parts to reduce processes and for improved design, and it is necessary to enable more complex forming.
[0003] If more complex press forming were to be performed, the steel plate could break due to being unable to withstand the forming, or die galling could occur during continuous press forming, which could have a serious adverse effect on automotive productivity.
[0004] One method for improving the press formability of cold-rolled steel sheets and hot-rolled steel sheets is to perform a surface treatment on the die. Although this method is widely used, the die cannot be adjusted after the surface treatment. In addition, this method has problems such as high costs. Therefore, there is a strong demand for improving the press formability of the steel sheet itself.
[0005] One method to improve press formability without surface treatment of the die is to use a high viscosity lubricant, but this can lead to poor degreasing after press forming, which can lead to poor paintability.
[0006] In response to this, various types of lubricant surface-treated steel sheets have been investigated as a technology that enables press forming without the need for surface treatment of dies or high-viscosity lubricants.
[0007] Patent Document 1 describes a metal sheet coated with a lubricating film in which a solid lubricant protrudes from the surface of a resin film by 0.01 to 1.5 μm.
[0008] Patent Document 2 describes a lubricating surface-treated metal product having excellent press formability, which is coated with a 0.5 to 5 μm thick film made of polyurethane resin containing a lubricant.
[0009] Patent Document 3 describes a technique for forming an alkali-soluble organic film, which is an epoxy resin containing a lubricant added thereto, on a steel sheet. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Application Publication No. 10-52881 [Patent Document 2] JP 2000-309747 A [Patent Document 3] JP 2000-167981 A Summary of the Invention [Problem to be solved by the invention]
[0011] However, in the techniques disclosed in Patent Documents 1 to 3, although lubricity is achieved by the lubricating effect of the contained lubricant or the like, press formability is not necessarily sufficient in complex forming.
[0012] The present invention has been made in consideration of the above circumstances, and aims to provide a steel sheet that is subjected to complex forming processes that are difficult to form by press forming, and that has low sliding resistance in areas at risk of cracking during press forming, and excellent press formability in areas where the surface pressure is high and mold galling is expected to occur.
[0013] Furthermore, when used as a steel sheet for automobiles, it is also required to have sufficient removability in the alkaline degreasing step in the painting process, and it is a further object of the present invention to provide a steel sheet for such applications that also has good removability. [Means for solving the problem]
[0014] The present inventors have conducted extensive research to solve the above problems. As a result, it has been found that in order to dramatically improve press formability, an organic resin film containing polyolefin wax having a melting point of 120°C to 140°C and an average particle size of 3.0 μm or less is formed on the surface of a steel sheet, and the standard deviation σ of the coating weight distribution per side of the organic resin film is 0.9 g / m 2 It was found that the above-mentioned problems can be solved by controlling the surface roughness and coating weight distribution of the steel sheet to specific ranges so as to satisfy less than 100%. It was also found that the press formability can be further improved by setting the coating weight, the arithmetic mean roughness Ra of the steel sheet, the average particle size of the wax, and the proportion of the wax in the coating within suitable ranges.
[0015] The present invention has been completed based on the above findings, and the gist of the present invention is as follows.
[0016] The base steel sheet refers to a portion of the steel sheet excluding the coating that exists as a base for the coating containing organic resin and wax. Also, the base steel sheet may be a cold-rolled steel sheet or a hot-rolled steel sheet. [1] A steel sheet comprising a steel sheet precursor and a coating formed on at least one side of the steel sheet precursor, the coating containing an organic resin and a wax, the arithmetic mean roughness Ra of the steel sheet precursor is 0.4 μm or more, the organic resin is at least one of an acrylic resin, an epoxy resin, a urethane resin, a phenolic resin, a vinyl acetate resin, and a polyester resin, the wax is a polyolefin wax having a melting point of 120° C. or more and 140° C. or less and an average particle size of 3.0 μm or less, the proportion of the wax in the coating is 10 mass % or more, and the standard deviation σ of the coating adhesion weight distribution per one side of the coating is 0.9 g / m 2 Less than steel plate. [2] The coating weight W of the coating on one side is 2.0 g / m 2 The steel sheet according to [1] below. [3] The steel sheet according to [1] or [2], wherein the arithmetic mean roughness Ra of the steel sheet is 0.4 μm or more and 2.5 μm or less. [4] The steel sheet according to any one of [1] to [3], wherein the wax has an average particle size of 0.01 μm or more and 0.5 μm or less. [5] The steel sheet according to any one of [1] to [4], wherein the proportion of the wax in the coating is less than 50 mass %. [6] The coating weight W of the coating on one side is 0.9 g / m 2 The steel sheet according to any one of the following [2] to [5]. [7] The steel sheet according to any one of [1] to [6], wherein the organic resin is an alkali-soluble resin. [8] A method for producing a steel plate according to any one of [1] to [7], comprising applying a coating material containing the organic resin and wax according to any one of [1] to [7] to at least one side of an original steel plate, and drying the coating material. [9] The method for manufacturing a steel sheet according to [8], wherein the viscosity of the paint is 1.5 mPa·s or more and 8.0 mPa·s or less.
[10] The method for manufacturing a steel plate according to [8] or [9], wherein the maximum temperature of the steel plate raw sheet during the drying is 60°C or more and 140°C or less, and the drying time during the drying is 2 seconds or more and 150 seconds or less. Effect of the Invention
[0017] According to the present invention, a steel sheet having excellent press formability can be obtained by significantly reducing the coefficient of friction between the steel sheet and a die, etc. Therefore, the steel sheet has stable and excellent press formability even when the steel sheet has a relatively low strength and is subjected to complicated forming.
[0018] Furthermore, even in high-strength steel plates that are subjected to increased surface pressure during press forming, it is possible to obtain a steel plate that has low sliding resistance in areas at risk of cracking during press forming and has excellent press formability in areas where the surface pressure is high and mold galling is expected to occur.
[0019] Furthermore, a steel sheet having good coating removability can be obtained.
[0020] In the above, high strength is assumed to have a tensile strength (TS) of 440 MPa or more, and relatively low strength is assumed to have a TS of less than 440 MPa. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a diagram showing the distribution of local coating weight when the difference in coating weight between the recessed portion and the protruding portion of the steel sheet is different. [Diagram 2] FIG. 2 is a diagram showing the distribution of local coating weights when the average coating weights are different. [Diagram 3] FIG. 3 is a diagram showing the distribution of local coating weight when the surface roughness of the steel sheet is different. [Figure 4] FIG. 4 is a schematic front view of the friction coefficient measuring device. [Diagram 5] FIG. 5 is a schematic perspective view showing the shape and dimensions of the bead in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, an embodiment of the present invention will be described.
[0023] The present invention is a steel sheet comprising a steel sheet precursor and a coating formed on at least one side of the steel sheet precursor, the coating containing an organic resin and a wax, the arithmetic mean roughness Ra of the steel sheet precursor is 0.4 μm or more, the organic resin is at least one of acrylic resin, epoxy resin, urethane resin, phenol resin, vinyl acetate resin, and polyester resin, the wax is a polyolefin wax having a melting point of 120° C. or more and 140° C. or less and an average particle size of 3.0 μm or less, and the proportion of the wax in the coating is 10 mass % or more. Furthermore, the standard deviation σ of the coating adhesion weight distribution per one side of the coating is 0.9 g / m 2 It is characterized in that the
[0024] The wax used in the present invention is not limited as long as it is a polyolefin wax having a melting point of 120° C. or higher and 140° C. or lower and an average particle size of 3.0 μm or less.
[0025] The reason why polyolefin wax is used as the wax is that it has low surface energy and self-lubricating properties, and therefore provides good lubrication. In addition, it is relatively easy to adjust the melting point of polyolefin to 120°C or higher and 140°C or lower by controlling the density and molecular weight.
[0026] When the melting point is 120°C or more and 140°C or less, in addition to the self-lubricating properties of the polyolefin wax itself, the wax becomes semi-molten due to sliding during press molding, and the lubricating film components mixed with the organic resin can cover the surface of the mold, and excellent lubrication effects can be obtained by suppressing direct contact between the mold and the steel plate. When the melting point is less than 120°C, the wax completely melts due to frictional heat caused by sliding during press molding, and the wax itself does not provide sufficient lubrication effect, and the above-mentioned mold coating effect cannot be obtained. Also, when the melting point exceeds 140°C, it does not melt during sliding, and sufficient lubrication effect cannot be obtained, and the mold coating effect cannot be obtained.
[0027] When the melting point of the wax is 120°C or more and 140°C or less, the wax in the film efficiently adheres to the die in the sliding state during press molding, and is less likely to fall off, which is thought to provide a high lubrication effect. When the melting point of the wax is less than 120°C, even if the film adheres to the die, the adhesion is weak, and the film is likely to fall off when slid. When the melting point of the wax is more than 140°C, the film is less likely to adhere to the die. Furthermore, it is preferable that the melting point of the wax is 125°C or more and 135°C or less.
[0028] The melting point of the wax herein refers to the melting temperature measured based on JIS K 7121:1987 "Method of measuring transition temperature of plastics". If the average particle size of the wax exceeds 3.0 μm, it becomes difficult to mix with the organic resin during sliding, and the above-mentioned coating effect of the mold cannot be obtained, and sufficient lubrication cannot be obtained. The average particle size of the wax is preferably 1.5 μm or less. The average particle size of the wax is more preferably 0.5 μm or less, and even more preferably 0.3 μm or less.
[0029] The wax particle size is preferably 0.01 μm or more. If the wax has an average particle size of less than 0.01 μm, it will be easily dissolved in the lubricating oil during sliding, and may not exhibit sufficient lubrication improvement effects, and it will be easily aggregated in the paint for forming the film, resulting in low paint stability. The wax average particle size is more preferably 0.03 μm or more.
[0030] The average particle size is the median diameter of the volume average diameter, and can be determined by a laser diffraction / scattering method, for example, by measuring a sample diluted with pure water using a laser diffraction / scattering type particle size distribution measuring device Partica (registered trademark) LA-960V2 (manufactured by Horiba, Ltd.).
[0031] Among polyolefin waxes, polyethylene wax is preferred because it provides the greatest lubricating effect.
[0032] The mass ratio of the wax in the film is 10% by mass or more. If the mass ratio of the wax in the film is less than 10% by mass, a sufficient lubricating effect cannot be obtained. If the mass ratio of the wax in the film is 15% by mass or more, a particularly good lubricating effect can be obtained. In addition, the mass ratio of the wax in the film is preferably less than 50% by mass. If the mass ratio of the wax in the film is 50% by mass or more, the wax is likely to fall off due to a shortage of the base resin component, and the adhesion to the steel sheet raw sheet may be poor, and the film may not exist stably. In addition, when used as a steel sheet for automobiles, sufficient degreasing may not be obtained in the alkaline degreasing step in the painting process, and even if an alkali-soluble organic resin is used, the film may not be sufficiently degreased in the alkaline degreasing step, and the film may remain, causing deterioration of paintability. The mass ratio of the wax in the film is more preferably 30% by mass or less.
[0033] Here, the proportion of wax in the coating refers to the proportion of the mass of the solid content of wax in the coating to the total mass of the solid content of the organic resin in the coating and the solid content of the wax in the coating.
[0034] As a specific measurement method, for the resin and wax, a test piece with a known amount of the coating on the steel sheet is prepared, the infrared absorption spectrum is measured with an FT-IR measurement device, and a calibration curve for the amount of the resin and wax is created from the peak intensity derived from each of the resin and wax. Next, the infrared absorption spectrum of the lubricating coating-coated steel sheet to be measured is measured, and the amount of the resin and wax is obtained from the calibration curve, so that the mass ratio of the wax in the coating can be obtained.
[0035] In the present invention, the organic resin plays the role of a binder that holds the wax on the surface of the steel sheet. The sliding effect caused by the mold coating with the mixture of wax and organic resin formed during sliding as described above is not exhibited by inorganic binders because of their low affinity with polyolefin. As the organic resin, at least one of acrylic resins, epoxy resins, urethane resins, phenolic resins, vinyl acetate resins, and polyester resins can be used.
[0036] The acrylic resin used in the present invention is a polymer or copolymer of one or more selected from unsaturated monocarboxylic acids having one carboxy group in the molecule, such as acrylic acid or methacrylic acid, esters of the above unsaturated monocarboxylic acids, and styrene, or a derivative thereof, such as a sodium salt, potassium salt, ammonium salt, or amine salt thereof.
[0037] Acrylic resins in which the monomer is a fatty acid with two or more carboxy groups in the molecule may have poor paint stability, so in the present invention, an acrylic resin in which the monomer is a fatty acid with one carboxy group in the molecule or a fatty acid ester thereof is used.
[0038] The epoxy resin is not particularly limited, but examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, and the like.
[0039] The urethane resin is not particularly limited, but preferably has a carboxy group in the molecule.
[0040] The phenolic resin is not particularly limited, but a resol-based phenolic resin that can be dissolved or dispersed in an aqueous solvent is preferred.
[0041] The vinyl acetate resin is not particularly limited, but it is preferable to use polyvinyl acetate.
[0042] The polyester resin is not particularly limited, but a polyester resin containing a monomer having a carboxy group as a constituent component is preferred.
[0043] These resins can also be used in combination of two or more kinds. Furthermore, by using an alkali-soluble organic resin, it becomes possible to remove the film by alkaline degreasing in the painting process, and the subsequent paintability becomes good.
[0044] In the present invention, a surface conditioner, a defoamer, a dispersant, etc. may be contained as components other than the organic resin and the wax. Also, a rust inhibitor for improving rust prevention may be added.
[0045] In the present invention, when the above-mentioned coating is formed on the surface of the steel sheet, a coating having a wide range of coating weights is formed on steel sheets having a wide range of surface roughness, and press formability is evaluated. The state of the coating is measured by an SEM or EPMA equipped with an X-ray spectrometer. As a result, the standard deviation σ of the coating weight distribution of the steel sheets on which the coating is formed is 0.9 g / m 2 It was found that stable and good press formability is achieved only in the region where
[0046] In general, the greater the surface roughness of the original steel sheet, the more likely it is that the coating will become thinner at the convex parts of the original steel sheet, and when press-molded, the coating will be scraped off by sliding with the die, exposing the underlying original steel sheet, making it difficult to obtain a lubricating effect.
[0047] However, by using the technology of the present invention, adhesion of the coating components to the die during sliding is promoted, and even if the roughness of the steel sheet raw material is high, the die side is protected and lubrication is not impaired.
[0048] The coating components present in the convex parts of the original steel sheet that come into contact with the die during press working are what primarily contribute to the sliding properties. Generally, when a coating paint is applied, the coating paint tends to accumulate in the concave parts of the original steel sheet, so the amount of coating attached to the convex parts of the original steel sheet and the concave parts of the original steel sheet are not uniform, and there is a tendency for the film thickness to be thin on the convex parts of the original steel sheet and thick on the concave parts of the original steel sheet.
[0049] Furthermore, even if the coating weight is the same, the coating weight on the protruding parts of the steel sheet may be greater or less depending on differences in paint properties such as paint wettability, and differences in application and drying conditions.
[0050] Furthermore, the state of the coating amount on the original steel sheet protrusions (hereinafter simply referred to as protrusions) and the original steel sheet recesses (hereinafter simply referred to as recesses) changes depending on the coating amount and the roughness of the underlying original steel sheet.
[0051] As shown in Figure 1, when the difference in coating weight between the convex and concave parts becomes large due to differences in paint properties, application conditions, etc., the coating weight of the convex parts that come into contact with the die during press molding decreases, and press moldability deteriorates. In this case, the peak width showing the distribution of the coating weight of the entire coating widens, and the standard deviation σ also increases.
[0052] Furthermore, as shown in FIG. 2, when the average coating weight changes, the peak showing the distribution of the coating weight of the entire coating changes as shown below.
[0053] When the average coating weight is low, the coating weight of the convex parts is insufficient, and press formability is reduced. In this case, the peak positions of the coating weight distribution of the convex parts and concave parts shift to the lower coating weight side, and the interval between the peaks of the convex parts and concave parts widens. This causes the peak width of the overall coating weight distribution to widen, and the standard deviation σ to increase.
[0054] On the other hand, when the average coating weight is high, the coating weight of the projections is also sufficient, improving press formability. In this case, the peak positions of the coating weight distribution of the projections and recesses both shift toward the higher coating weight side, and the distance between the peaks of the projections and recesses narrows. As a result, the peak width of the overall coating weight distribution narrows, and the standard deviation σ also becomes smaller.
[0055] Furthermore, as shown in Figure 3, the width of the peak indicating the total coating weight also changes when the roughness of the base steel sheet changes. When the roughness of the base steel sheet is small, the variation in the coating weight distribution of the convex and concave portions is reduced, and the coating weight of the convex portions is stabilized, improving press formability. In this case, the peak width of the coating weight distribution of the convex and concave portions becomes smaller, and the peak width of the total coating weight distribution also becomes narrower. As a result, the standard deviation σ value also becomes smaller. Conversely, when the roughness of the steel sheet is large, the variation in the coating weight at the protrusions increases, resulting in poor press formability. In this case, the peak width of the coating weight distribution at the protrusions and recesses increases. As a result, the peak width of the overall coating weight distribution also increases, and the standard deviation σ also increases.
[0056] As described above, due to various factors, it becomes impossible to stably ensure the amount of coating adhered to the protruding parts that come into contact with the die, and press formability deteriorates.
[0057] When the coating weight on the protrusions is stable and the press formability is good, the standard deviation σ of the coating weight distribution of the entire coating will be small, and when the coating weight on the protrusions is not stable and the press formability is poor, the standard deviation σ will be large.
[0058] Therefore, if it is possible to evaluate the magnitude of the standard deviation σ of the coating weight distribution, it becomes possible to judge whether the press formability is good or bad.
[0059] The standard deviation σ of the coating weight distribution was calculated by measuring the intensity map of C-Kα radiation, which is the main component of the coating, and Fe-Kα radiation, which is the main component of the base steel sheet, using a SEM equipped with an X-ray spectrometer, and calculating the average value μ C / Feand standard deviation σ C / Fe It can be evaluated by calculating
[0060] Average value μ C / Fe is roughly proportional to the amount of coating, so μ C / Fe By comparing the coating weight with the standard deviation σ C / Fe can be converted into the standard deviation σ of the coating weight distribution.
[0061] The calibration curve for converting the characteristic X-ray intensity ratio into the coating weight is the average μ C / Fe The coating weight measured by the gravimetric method when is 0 is 0, that is, the intercept is the origin, and the average μ C / Fe The straight line connecting the points obtained by the above is used. The coating weight is measured by the gravimetric method, where the organic resin-coated steel sheet is immersed in an alkaline solution to dissolve only the organic resin portion, and the weight of the steel sheet before and after dissolution is measured, along with the area of the original steel sheet on which the coating was formed. The average characteristic X-ray intensity ratio μ C / Fe is the standard deviation of the coating weight distribution within the same sample σ C / Fe is the average value of all measured data.
[0062] When using the characteristic X-ray map for evaluation, it is necessary to set the accelerating voltage high enough so that the incident electrons can reach the underlying steel sheet even in recesses where the coating is thick, and so that Fe-Kα rays with sufficient intensity are generated. To achieve this, measurements should be performed at an accelerating voltage of 10 kV or higher.
[0063] However, if the accelerating voltage is too high, the efficiency of C-Kα radiation generation decreases, resulting in a decrease in intensity, so it is desirable to perform observations at 20 kV or less.
[0064] In addition, the measurement range and analysis point size of the strength map used in this evaluation must be measured so that they are statistically significant relative to the uneven shape of the steel plate surface. In the case of a steel plate with a surface roughness of approximately 1 μm, the diameter of the convex parts is approximately 50 μm, so it is desirable for the measurement range to be 200 μm x 200 μm so that 10 or more convex parts are included in the measurement range. In addition, it is desirable for the analysis point size to be 10 μm or less so that 10 or more points can be measured for each convex part.
[0065] The measurement field of view for the intensity map may be measured continuously or in any number of fields of view so long as the measurement range and analysis point size satisfy the above conditions.
[0066] The relationship between the standard deviation σ of the coating weight distribution calculated as above and the friction coefficient of the coating measured separately was investigated, and the standard deviation σ was found to be 0.9 g / m 2 It has been found that the coefficient of friction is good when the friction coefficient is less than 100 μm.
[0067] The coating weight W per side is 2.0g / m 2 The coating weight W per one side of the coating is preferably 2.0 g / m or less. 2 If it exceeds this value, the film removal may be poor. The film adhesion weight W per side of the film is 1.5 g / m 2 More preferably, it is 0.9 g / m or less. 2 It is particularly preferable that the coating weight W per one side of the coating is 0.9 g / m or less. 2 If it is equal to or less than this, the film removal property is particularly good.
[0068] The coating weight can be determined by a method in which the difference in weight of the steel sheet before and after coating is divided by the area, or by a method in which the coating of the steel sheet after coating is completely removed with an alkaline aqueous solution or an organic solvent, and then the difference in weight of the steel sheet before and after coating removal is divided by the area.
[0069] The arithmetic mean roughness Ra of the raw steel sheet is set to be 0.4 μm or more, and preferably, the arithmetic mean roughness Ra of the raw steel sheet is set to be 2.5 μm or less.
[0070] If the arithmetic mean roughness Ra of the steel sheet is less than 0.4 μm, fine scratches that may occur during press forming may be easily noticeable, and galling may occur during press forming. If it exceeds 2.5 μm, the required coating weight may become large, increasing manufacturing costs and deteriorating image clarity after painting.
[0071] The arithmetic mean roughness Ra (μm) of the steel sheet can be measured according to JIS B 0633:2001 (ISO 4288:1996). For example, when Ra is greater than 0.1 and less than 2, the cutoff value and reference length are set to 0.8 mm, the evaluation length is set to 4 mm, and the roughness is determined from the measured roughness curve. When Ra is greater than 2 and less than 10, the cutoff value and reference length are set to 2.5 mm, and the evaluation length is set to 12.5 mm, and the roughness is determined from the measured roughness curve.
[0072] Next, a method for producing a steel sheet according to the present invention will be described.
[0073] The method for producing a steel sheet of the present invention is a method for producing a steel sheet having an organic resin coating on the surface of an original steel sheet, the coating containing a polyolefin wax having a melting point of 120°C to 140°C and an average particle size of 3.0 μm or less. A paint in which an organic resin is dissolved or dispersed in a solvent, or a paint in which wax has been added to either of these, is applied to the surface of the original steel sheet and dried. Here, the paint is adjusted so that C, where MA is the mass of the solid content of the organic resin and MB is the mass of the solid content of the wax, C={MB / (MA+MB)}×100, is 10 mass% or more.
[0074] The mass ratio of the coating components (organic resin and polyolefin wax) in the coating material is preferably 1 mass % or more and 25 mass % or less.
[0075] The solvent for the paint is water or an organic solvent.
[0076] If the mass ratio of the coating component in the paint is less than 1% by mass or more than 25% by mass, unevenness may occur during application. The application method is not particularly limited, but examples include a method using a roll coater or a bar coater, and a method of application by spraying, immersion, or brushing. The steel sheet after application can be dried by a general method. For example, drying by hot air, drying by an IH heater, or a method by infrared heating may be included. The maximum temperature reached by the steel sheet during drying is preferably 60°C or higher and 140°C or lower. If the temperature is lower than 60°C, it takes a long time to dry and the rust prevention properties may be poor. If the temperature exceeds 140°C, the wax may melt and combine, causing the particle size to become coarse, which may deteriorate the lubricity, and in addition, the polymerization of the resin may proceed too far, which may reduce the film removal properties.
[0077] In the steel sheet manufacturing method of the present invention, the standard deviation σ of the coating weight distribution is 0.9 g / m 2 As a result, a steel sheet having good press formability can be produced.
[0078] As an example of the coating process being carried out during operation, 2 The coating weight W (g / m2) per side of the coating is set to less than 2 ) or the viscosity of the paint or the coating conditions. Such a manufacturing condition determination method may be carried out as a part of the process of the steel sheet manufacturing method, or may be carried out as an independent process.
[0079] Specifically, by increasing the coating weight per side of the coating, the difference in coating weight between the convex and concave portions of the steel sheet becomes smaller, and the standard deviation σ of the coating weight distribution can be reduced. From this perspective, the coating weight W per side is set to 0.3 g / m 2 It is preferable that the density is 0.5 g / m or more. 2 However, if the coating weight W is too high, the coating removal property may deteriorate as described above, so the coating weight W per side is preferably 2.0 g / m or more. 2 The coating weight W per side is preferably 1.5 g / m or less. 2Less than 0.9 g / m is more preferable. 2 In addition, if the viscosity of the coating material is too low, the coating material will tend to accumulate in the recesses, and the coating material will have a thinner liquid film thickness on the protrusions, resulting in a standard deviation σ of the coating weight distribution of 0.9 g / m 2 From this perspective, it is preferable for the viscosity of the paint to be 1.5 mPa s or more. On the other hand, if the viscosity of the paint is too high, the paint is more likely to be applied unevenly, and streaks and other patterns may appear after the film is formed, resulting in a poor appearance. For this reason, it is preferable for the viscosity of the paint to be 8.0 mPa s or less.
[0080] Furthermore, if the drying time of the coating is long, the paint spreads while drying, and the paint is likely to accumulate in the recesses, and the liquid film thickness of the paint on the protrusions becomes thin, and the thin film area ratio of the coating may become 25% or more. Therefore, by increasing the drying temperature as much as possible and shortening the drying time within a range that satisfies the target properties of the coating, it is possible to make the thin film area ratio of the coating 25% or less. The drying temperature is preferably 60°C or more, and particularly preferably 80°C or more. On the other hand, as described above, if the drying temperature exceeds 140°C, the wax melts and combines, and the particle size becomes coarse, which may deteriorate the lubricity, so the drying temperature is preferably 140°C or less. In addition, the drying time is preferably 150 seconds or less, more preferably 120 seconds or less, and particularly preferably 60 seconds or less. However, if the drying time is too short, the paint may not dry sufficiently and the corrosion resistance may decrease, so the drying time is preferably 2 seconds or more, and particularly preferably 4 seconds or more.
[0081] As described above, by appropriately controlling the coating weight per side, the viscosity of the paint, and the drying time of the paint, the standard deviation σ of the coating weight distribution can be reduced to 0.9 g / m 2 It can be less than. EXAMPLES
[0082] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0083] Cold-rolled steel sheets (steel sheets Nos. A to C) with a thickness of 0.8 mm and hot-rolled steel sheets (steel sheets Nos. D, E, and F) with a thickness of 2.0 mm and having the arithmetic mean roughness Ra shown in Table 1 were used as the steel sheet base sheets, and paints with the compositions shown in Table 2 were applied with a bar coater and dried with an IH heater so that the maximum temperature of the steel sheet base sheets reached 80°C, thereby obtaining steel sheets on which a coating containing organic resin and wax was formed. Note that all of the steel sheet base sheets A to F are SPCD or SPHD with tensile strengths of the 270 MPa class.
[0084] [Table 1]
[0085] [Table 2]
[0086] (1) Method for evaluating press formability (sliding characteristics) In order to evaluate the press formability of the obtained steel sheets, the friction coefficients of the steel sheets were measured as follows.
[0087] FIG. 4 is a schematic front view showing a friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1 taken from the obtained steel plate is fixed to a sample stage 2, and the sample stage 2 is fixed to the upper surface of a horizontally movable slide table 3. A slide table support base 5 that can move up and down and has a roller 4 in contact with the slide table 3 is provided on the lower surface of the slide table 3, and a first load cell 7 is attached to the slide table support base 5 to measure the pressing load N applied by the bead 6 to the friction coefficient measuring sample 1 by pushing up the slide table 3. A second load cell 8 is attached to one end of the slide table 3 to measure the sliding resistance force F for moving the slide table 3 in the horizontal direction while the pressing force is applied. The test was performed by applying press cleaning oil Pleton (registered trademark) R352L manufactured by Sugimura Chemical Industry Co., Ltd. as a lubricant to the surface of the sample 1.
[0088] Figure 5 is a schematic perspective view showing the shape and dimensions of the bead used. The bead 6 slides while its underside is pressed against the surface of the sample 1. The shape of the bead 6 shown in Figure 5 is 10 mm wide, 59 mm long in the sliding direction of the sample, and the lower parts of both ends in the sliding direction are curved surfaces with a curvature of 4.5 mmR, and the underside of the bead against which the sample is pressed has a flat surface with a width of 10 mm and a length of 50 mm in the sliding direction.
[0089] The friction coefficient measurement test was performed using the bead shown in Figure 5, with a pressing load N of 400 kgf and a sample pull-out speed (horizontal movement speed of the slide table 3) of 20 cm / min. The friction coefficient μ between the test material and the bead was calculated by the formula: μ = F / N.
[0090] A friction coefficient of 0.119 or less was evaluated as being particularly excellent in terms of sliding properties, as ⊚. A friction coefficient of more than 0.119 and less than 0.130 was evaluated as being good in terms of sliding properties, as ◯. A friction coefficient of more than 0.130 was evaluated as being insufficient, as x.
[0091] (2) Evaluation method for film removal Assuming that the steel sheet according to the present invention is used in automotive applications, the degreasing property of the steel sheet during degreasing was evaluated. In order to determine the degreasing property of the steel sheet, first, each test piece taken from the obtained steel sheet was degreased with an alkaline degreaser Fine Cleaner (registered trademark) E6403 (manufactured by Nihon Parkerizing Co., Ltd.). In this treatment, the test piece was immersed in a degreasing solution with a degreaser concentration of 20 g / L and a temperature of 40° C. for a predetermined period of time, and then washed with tap water. The surface carbon intensity of the test piece after this treatment was measured using a fluorescent X-ray analyzer, and the coating peeling rate was calculated according to the following formula using this measured value, the surface carbon intensity before degreasing that was previously measured, and the surface carbon intensity of the untreated steel sheet.
[0092] Film peeling rate (%) = [(carbon strength before degreasing - carbon strength after degreasing) / (carbon strength before degreasing - carbon strength of untreated steel plate)] x 100 The removability of the steel sheet was evaluated according to the following criteria based on the immersion time in the alkaline degreasing solution at which the film peeling rate was 98% or more. The removability was judged to be acceptable in the cases of ◎, ◯, and △. ◎ (particularly good): Within 15 seconds ○ (Good): More than 15 seconds, less than 45 seconds △ (Pass): Over 45 seconds and under 120 seconds × (bad): Over 120 seconds (3) Method for evaluating the standard deviation σ of the coating weight The standard deviation σ of the coating weight of the obtained steel sheet was measured as follows.
[0093] Five small pieces of 10 mm square were cut from each of the obtained steel sheets as test materials. For the measurements, a Schottky field emission SEM (Σigma, manufactured by Carl Zeiss) equipped with an energy dispersive X-ray spectrometer (XFlash5|30, manufactured by Bruker) was used.
[0094] For each steel plate level, five test pieces were measured near the center of the specimens, with a magnification of 300x, and C-Kα and Fe-Kα intensity maps were measured at 800 x 600 measurement points, with an acceleration voltage of 15 kV. The measured C Kα intensity map was divided by the corresponding Fe-Kα intensity map to calculate the C-Kα / Fe-Kα intensity ratio map. Furthermore, the average value μ of the C-Kα / Fe-Kα intensity ratio was calculated from the intensity ratio map. C / Fe and standard deviation σ C / Fe The average value of five visual fields was used for evaluation. C / Fe From the relationship between the amount of coating and the standard deviation of the C-Kα / Fe-Kα intensity ratio, σ C / Fe was converted to the standard deviation σ of the coating weight. σ calculated as above was 0.9 g / m 2 If it was less than 0.9 g / m, it was considered good (○); 2 In the above cases, the sample was evaluated as defective (×).
[0095] [Table 3]
[0096] [Table 4]
[0097] [Table 5]
[0098] According to Tables 3 to 5, the steel sheets of the examples of the present invention all have excellent press formability. In contrast, the steel sheets of the comparative examples not having the technical features of the present invention all have poor press formability. In addition, when the mass ratio of wax in the coating is less than 50 mass % and the coating amount per side is 2.0 g / m 2 By doing the following, excellent coating removal properties were obtained. [Industrial Applicability]
[0099] The steel sheet of the present invention has excellent press formability and coating removal property, and can be applied in a wide range of fields, mainly in automobile body applications. [Explanation of symbols]
[0100] 1. Sample for measuring friction coefficient 2 Sample stage 3 Slide table 4. Lola 5 Slide table support 6 Beads 7 First load cell 8 Second Load Cell 9. Rail
Claims
1. A steel sheet comprising a steel sheet raw material and a coating formed on at least one surface of the steel sheet raw material, the coating comprises an organic resin and a wax; The arithmetic average roughness Ra of the steel sheet is 0.4 μm or more, the organic resin is at least one of an acrylic resin, an epoxy resin, a urethane resin, a phenol resin, a vinyl acetate resin, and a polyester resin; The wax is a polyolefin wax having a melting point of 120° C. or higher and 140° C. or lower and an average particle size of 3.0 μm or less, The proportion of the wax in the coating is 10 mass% or more, The coating weight per one side of the coating is 0.25 g / m 2 or more; The standard deviation σ of the coating weight distribution per side of the coating is 0.9 g / m 2 is less than In measuring the standard deviation σ of the coating weight distribution, the analysis point size is 10 μm or less when measuring intensity maps of C-Kα radiation and Fe-Kα radiation at a magnification of 300 times from the vicinity of the center of five test pieces for each steel plate level, at an acceleration voltage of 15 kV and 800 x 600 measurement points.
2. The coating weight W per side of the coating is 2.0 g / m 2 The steel sheet according to claim 1, wherein:
3. The steel sheet according to claim 1, wherein the raw steel sheet has an arithmetic mean roughness Ra of 0.4 μm or more and 2.5 μm or less.
4. The steel sheet according to claim 2, wherein the original steel sheet has an arithmetic mean roughness Ra of 0.4 μm or more and 2.5 μm or less.
5. The steel sheet according to claim 1, wherein the wax has an average particle size of 0.01 μm or more and 0.5 μm or less.
6. The steel sheet according to claim 2, wherein the wax has an average particle size of 0.01 μm or more and 0.5 μm or less.
7. The steel sheet according to claim 3, wherein the wax has an average particle size of 0.01 μm or more and 0.5 μm or less.
8. The steel sheet according to claim 4, wherein the wax has an average particle size of 0.01 μm or more and 0.5 μm or less.
9. The steel sheet according to claim 1 , wherein the proportion of the wax in the coating is less than 50 mass %.
10. The steel sheet according to claim 2 , wherein the proportion of the wax in the coating is less than 50 mass %.
11. The steel sheet according to claim 3 , wherein the proportion of the wax in the coating is less than 50 mass %.
12. The steel sheet according to claim 5 , wherein the proportion of the wax in the coating is less than 50 mass %.
13. The steel sheet according to claim 6 , wherein the proportion of the wax in the coating is less than 50 mass %.
14. The steel sheet according to claim 7 , wherein the proportion of the wax in the coating is less than 50 mass %.
15. The coating weight W per one side of the coating is 0.9 g / m 2 The steel sheet according to claim 2, wherein:
16. The steel sheet according to claim 1 , wherein the organic resin is an alkali-soluble resin.
17. A method for producing a steel plate according to any one of claims 1 to 16, comprising applying a coating material containing the organic resin and wax according to any one of claims 1 to 16 to at least one surface of an original steel plate, and drying the coating material.
18. The method for manufacturing a steel sheet according to claim 17, wherein the paint has a viscosity of 1.5 mPa·s or more and 8.0 mPa·s or less.
19. The method for producing a steel sheet according to claim 17, wherein a maximum temperature of the raw steel sheet during the drying is 60° C. or more and 140° C. or less, and a drying time during the drying is 2 seconds or more and 150 seconds or less.
20. The method for producing a steel sheet according to claim 18, wherein a maximum temperature of the raw steel sheet during the drying is 60° C. or more and 140° C. or less, and a drying time during the drying is 2 seconds or more and 150 seconds or less.
Citation Information
Patent Citations
Resin coated composite steel plate excellent in after-processing appearance
JP1993077357A
Galvanized steel sheet covered with alkali-soluble resin coating film having excellent adhesiveness by adhesive
JP1997170059A
Resin coated metal plate with mold drag resistance and corrosion resistance and its manufacture
JP1998052881A
Alkali-soluble type organic film-coated steel sheet having excellent adhesiveness and anti-mold galling property
JP2000167981A
Coating composition having ability to form lubricative film excellent in press-moldability and scuffing- resistance, and of alkali-soluble type, and metal product having lubricatively treated surface using this composition
JP2000309747A